1991
DOI: 10.1055/s-0038-1646389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Concentrated Ethylester Compound of n-3 Fatty Acids on Lipids, Platelets and Coagulation in Patients Undergoing Coronary Bypass Surgery

Abstract: SummaryTwenty patients accepted for coronary bypass surgery were randomized to receive either a concentrated ethylester compound of n-3 fatty acids, with a daily dose of 3.15 g of eicosapentaenoic acid (EPA) and 1.89 g of docosahexaenoic acid (DHA), or corn oil (controls) in a double blind study, to evaluate the effect on lipids, platelets and coagulation during the pre- and postoperative phase.Only patients with fasting triglyceride (TG) levels ≥1.6 mmol/1 at recruitment were eligible. The study was continued… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
(34 reference statements)
2
28
0
Order By: Relevance
“…20 In a study by Vanschoonbeek et al, 21 4 weeks of fish oil treatment resulted in reduced thrombin generation and fibrinogen levels in healthy volunteers; however, the effect was variable and more pronounced in those with a structural fibrinogen alpha-chain polymorphism. Very recent studies have suggested that exogenous modification of platelet membranes by omega-3 fatty acids results in decreased platelet procoagulant activity and thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…20 In a study by Vanschoonbeek et al, 21 4 weeks of fish oil treatment resulted in reduced thrombin generation and fibrinogen levels in healthy volunteers; however, the effect was variable and more pronounced in those with a structural fibrinogen alpha-chain polymorphism. Very recent studies have suggested that exogenous modification of platelet membranes by omega-3 fatty acids results in decreased platelet procoagulant activity and thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…Prostacyclin, a vasodilator eicosanoid, is produced from the ω‐6 PUFA, AA, and the ω‐3 PUFA, EPA, whereas the active form of the vasoconstrictor, thromboxane, is only produced from the ω‐6 PUFA, AA. It is widely accepted that a low ratio of EPA/AA predisposes to a balance of eicosanoids, favoring vasoconstriction, platelet aggregation, inflammatory mediator signaling and cardiac arrhythmias 16,18–23 . During acute stress, augmented free radical production, peroxidation of ω‐6 PUFA, and production of specific prostanoids, leukotrienes, cytokines, and other inflammatory mediators promote metabolic, ionic, and electrical instability, and depress contractile dysfunction 18–23 .…”
Section: Altered Metabolic Adaptation and Response To Injurymentioning
confidence: 99%
“…It is widely accepted that a low ratio of EPA/AA predisposes to a balance of eicosanoids, favoring vasoconstriction, platelet aggregation, inflammatory mediator signaling and cardiac arrhythmias. 16,[18][19][20][21][22][23] During acute stress, augmented free radical production, peroxidation of -6 PUFA, and production of specific prostanoids, leukotrienes, cytokines, and other inflammatory mediators promote metabolic, ionic, and electrical instability, and depress contractile dysfunction. [18][19][20][21][22][23] Recently it has been shown in CABG surgery patients that epicardial adipose tissue around the proximal coronary arteries is a rich source of inflammatory cytokines, such as IL-6, IL-1␤, TNF-␣, and that surgery promotes their release.…”
Section: Altered Metabolic Adaptation and Response To Injurymentioning
confidence: 99%
“…60,111 Moreover, changes in levels of fibrinogen, factor VII or VIII, or von Willebrand factor generally did not significantly differ between recipients of 1000-6000 mg/day omega-3 EE and controls in healthy volunteers, 112 post-MI patients, 110 patients with mild hypertension, 81 patients with combined hyperlipidemia 109 or patients undergoing coronary artery bypass graft (CABG) surgery. 113 Bleeding time was prolonged in 40 post-MI patients after four weeks of 3400 mg/day EPA-DHA, without significant alteration of other hemostatic parameters, 114 and increased in one study in CAD patients. 115 At variance with previous studies, omega-3 EE 6000 mg/day did not affect bleeding time at rest in patients with familial hypercholesterolemia, 100,113 or in patients undergoing CABG surgery.…”
Section: Dovepressmentioning
confidence: 99%
“…113 Bleeding time was prolonged in 40 post-MI patients after four weeks of 3400 mg/day EPA-DHA, without significant alteration of other hemostatic parameters, 114 and increased in one study in CAD patients. 115 At variance with previous studies, omega-3 EE 6000 mg/day did not affect bleeding time at rest in patients with familial hypercholesterolemia, 100,113 or in patients undergoing CABG surgery.…”
Section: Dovepressmentioning
confidence: 99%